Role of Copeptin in predicting of Major Adverse Cardiovascular Events (MACE) during Hospitalization on Acute Myocardial Infarction Patients - Wasyanto, Trisulo; Raynantha, I Putu; Yasa, Ahmad (Indonesian Journal of Medicine, 2021)
Background: Copeptin has been considered as a potential biomarker for AMI which also give information regarding the prognostic of the Acute myocardial infarction (AMI). The aim of this study is to understand the role of copeptin as a predictor of major adverse cardiovascular events (MACE) during hospitalization in AMI patients.Subjects and Method: This was a cohort analytical study conducted at Dr. Moewardi Hospital, Surakarta, from March to May 2021. The dependent variable was MACE. The independent variable was the copeptin level. We observe the MACE during hospitalization and analyze the cut-off point value for optimal copeptin levels to predict the occurrence of MACE using the receiver operating characteristic (ROC) curve. Linear multiple regression was conducted to predict determinants of MACE in hospitalization patients.Results: 52 patients recruited in this research (44 males, 8 females). During hospitalization, MACE occurred in 52% of these subjects, with the respective proportions for acute heart failure, cardiogenic shock, arrhythmias, cardiopulmonary resuscitation, and mortality of 28%, 10%, 8%, 4%, and 2%. The ROC curve showed that the cut-off point of copeptin was 2,141.50 pg/mL and area under curve (AUC) value of 0.710 with sensitivity of 75.0%, specificity of 68.80% and accuracy of 71.15%. Hence, the AUC values and accuracy present fair results for predicting MACE during hospitalization in AMI patients.Conclusion: Copeptin has a role as a predicttor of MACE during hospitalization in AMI patients.Keywords: copeptin, mayor adverse cardiovascular events, acute myocardial infarctionCorrespondence: Trisulo Wasyanto. Department of Cardiology and Vascular Medicine, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital. Jl. Kol. Sutarto 132, Surakarta 57126, Central Java. Email: trisulo.wasyanto@gmail.com.Indonesian Journal of Medicine (2021), 06(02): 230-238https://doi.org/10.26911/theijmed.2021.06.02.12.